Luck of the withdrawal. Issue 5 (October 2016) - Rogers, Jennifer
Abstract : What are the chances that you find yourself withdrawing a £10 note that was signed a decade ago by a work colleague? It happened to a BBC employee, and Jennifer Rogers was called in to calculate the probabilities. Abstract : What are the chances that you find yourself withdrawing a £10 note that was signed a decade ago by a work colleague? It happened to a BBC employee, andJennifer Rogers was called in to calculate the probabilities